Assessment of Water, Sanitation, and Hygiene in South-East Asia: A Systematic Review - Deepak Kumar Behera; Kalolini D Samant; Ranjit Kumar Dehury (Journal of Clinical and Diagnostic Research, 2022)
Introduction: Water, Sanitation and Hygiene (WASH) can be used as an indicator for the assessment of the health of a country. Without WASH facilities, it is very difficult for the sustenance of health and well-being of the people. Aim: This systematic review tries to bring out various nuances of practices on WASH and their intervention in the South-East Asia Region (SEAR). Materials and Methods: In the present systematic review, searches were made systematically in scholarly sources like Google Scholar, PubMed and Science Direct to unearth data from January 2005 to February 2020 with a language restriction to English for all the published articles. The literature search was conducted from March to May, 2020. The full-text articles (accessible) were retrieved from each of the searches and a few of the papers which appeared to be relevant were obtained for review. Articles were included from both urban and rural set-ups. Irrelevant topics and headings were excluded. The final review included 15 articles. Results: The area of SEAR has a different level of practice and outcomes on WASH. The studies show that low-quality WASH practices in Bangladesh, India and Sri Lanka contribute to public health issues. The studies on the health impact of WASH from many countries like Indonesia, Myanmar, Sri Lanka and Timor-Leste are also found to be inadequate in the maintenance of health. The report mentioned about many diseases like gastroenteritis, stunting and helminthes infection among many people in the community. The source of drinking water and drinking water quality needs to be assessed according to the recommendation of studies across the SEAR region. Two infectious diseases recently emerged such as Soil Transmitted Helminths (STH) and Escherichia coli contamination due to inadequate WASH practices. Conclusion: The diarrhoeal diseases and sanitation related issues are numerous in the entire region. Diverse consumption of sanitary practices and drinking water is seen in India, as reported in one study; whereas open defecation has not been eliminated as reported in another study, where 32% of households are still defecating openly. Health impacts due to the lack of proper WASH practices are still a rising concern. Special attention is required for underprivileged areas like slums and rural areas. The involvement of the government in providing WASH facilities to underprivileged people is very significant.